ENVIRONMENTAL CERTIFICATION AS A FACTOR INCREASING THE COMPETITIVENESS OF THE HOTEL AND RESTAURANT BUSINESS - Свідло, Карина; Мамченко, Людмила; Соколенко, Анна (Modern engineering and innovative technologies, 2022)
The article considered the prospects of greening the hotel business on the example of the 5-star Kharkiv Palace hotel. A comprehensive assessment of the benefits received by hotel enterprises around the world as a result of environmental certification is